Domestic violence and mandatory arrest : influences on police officer actions - Waldron, John F. (John Francis), 1954- (Criminal justice (LFB Scholarly Publishing LLC), 2012)
Despite mandates requiring annual in-service training on domestic violence for all New Jersey police officers, many officers do not receive this training. In-service training enhances the enforcement of domestic violence laws. Police officers in New Jersey, a mandatory arrest jurisdiction for the enforcement of domestic violence laws, rely heavily on their perception of the law to justify their enforcement activities. Victim's wishes and opinions on the enforcement of domestic violence laws have little effect on the arrest outcome in mandatory arrest jurisdictions, such as New Jersey, according to both officer's opinions and their reactions to hypothetical situations in this study.